Clinical actionability and utilization of next-generation sequencing for prostate cancer in a changing treatment landscape - Griffin, Jacqueline; Tsao, Che-Kai; Patel, Vaibhav; Liaw, Bobby C.; Guin, Sunny; Joshi, Himanshu; Rossi, Michael; Hantash, Feras; Zhou, Xiang; Tewari, Ash; Galsky, Matthew D.; Oh, William K.; et al. (Frontiers in Urology, 2022)
Background: Until recently there were no genome-directed therapies (GDTs) requiring next-generation sequencing (NGS) in prostate cancer. We examined whether the US approval of poly-(ADP-ribose) polymerase (PARP) inhibitors in May 2020 influenced the actionability and utilization of NGS in patients with prostate cancer. Methods: This was a single-center, retrospective study including men with prostate cancer who received NGS testing from a single lab between 7/11/2018-7/6/2021. Clinical and testing data were derived from the electronic medical record. Results: There were 346 patients with prostate cancer and qualifying NGS testing during the study period. Overall, 55 patients (15.9%) had qualifying homologous recombination repair (HRR) alterations for PARP inhibitor treatment. A greater proportion of alterations were actionable post-approval compared to pre-approval (22.7% vs 0%, Chi-squared p<0.001). 9 patients received olaparib during the study period. Patients receiving NGS testing after the PARP inhibitor approval were more likely to have metastatic disease than patients sequenced before the approval (74.2% vs. 41.1% Chi-squared p<0.001). Only 10.4% of patients with metastatic prostate cancer received NGS testing within 30 days of diagnosis. NGS testing was performed after a median of 1 prior line of systemic therapy. The median number of days between metastatic diagnosis and NGS testing was 196 (Q1-Q3: 54-832). The median time from NGS testing to the next treatment was 255 days (95% CI 151-300). These characteristics were not significantly different before or after the PARP inhibitor approval. Conclusion: In this single-center cohort, the approval of PARP inhibitors for later-line treatment of metastatic prostate cancer increased the actionability of NGS findings but did not lead to earlier use of NGS testing.